A clear view of the law: Making sense of legal complexity - LOW, Kee Yang (Institutional Knowledge at Singapore Management University, 2021)
Most of us find law complex and, sometimes, incomprehensible. Yet, we encounter a host of different laws as we go about our daily lives. So, how then do we navigate the intricate pathways of laws that are relevant to us if we do not know what they mean, how to apply them or how to avoid the pitfalls? This book allows us to bridge that gulf of understanding. Written in a simplified manner, the author shows us what law is, how laws are crafted and helps us understand its complexities and imperfections so that we come away with a clear view of the law.